2013
DOI: 10.4028/www.scientific.net/kem.587.97
|View full text |Cite
|
Sign up to set email alerts
|

Traversing Phase Fields towards Nanosized Beta Tricalcium Phosphate

Abstract: The difficulty of beta tricalcium phosphate (β-TCP) crystallization in aqueous media opens the question whether β-TCP can be produced using an alternative pathway. Amorphous calcium phosphate (ACP) is metastable in an aqueous environment and prefers a more stable apatite phase. Others have transformed a crystallized calcium deficient hydroxyapatite (Ca-def HAp) into β-TCP, but automatic transformation from ACP to Ca-def HAp followed by transformation to β-TCP has not been addressed. This work shows the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…The structural characterization of the CPPs used a combination of XRD, FTIR, and 31 P MAS NMR techniques. The XRD pattern of the as-prepared CPPs (Figure A) shows three broad reflections observed between 20 and 60 degrees 2θ, which indicates the amorphous nature of these particles as reported in the literature. Figure B shows that the nature of bonding in the CPPs can be determined by FTIR. All bands are assigned according to previous literature reports. , Specifically, the bands measured at 540, 730, 790, and 900 cm –1 are all assigned to vibrational and stretching modes of the P–O–P bonding.…”
Section: Resultssupporting
confidence: 62%
“…The structural characterization of the CPPs used a combination of XRD, FTIR, and 31 P MAS NMR techniques. The XRD pattern of the as-prepared CPPs (Figure A) shows three broad reflections observed between 20 and 60 degrees 2θ, which indicates the amorphous nature of these particles as reported in the literature. Figure B shows that the nature of bonding in the CPPs can be determined by FTIR. All bands are assigned according to previous literature reports. , Specifically, the bands measured at 540, 730, 790, and 900 cm –1 are all assigned to vibrational and stretching modes of the P–O–P bonding.…”
Section: Resultssupporting
confidence: 62%
“…The broad peaks in the XRD patterns of the as‐prepared microspheres may indicate that the material was poorly crystallized, or consisted of nanometer‐sized crystals, or a combination of both. These patterns are typical for CDHA 36,37 . The intensity of the peaks increased markedly for the heat‐treated microspheres, presumably as the result of increased crystal fraction or crystal size.…”
Section: Resultsmentioning
confidence: 75%
“…These patterns are typical for CDHA. 36,37 The intensity of the peaks increased markedly for the heat-treated microspheres, presumably as the result of increased crystal fraction or crystal size. The XRD patterns of heat-treated microspheres indicate the presence of various weight ratios of HA and β-TCP.…”
Section: Micro-and Mesostructures Of As-prepared and Heat-treated Hol...mentioning
confidence: 98%
“…Sirirat et al (2013) reported that addition of nano -chromium picolinate to laying hens diets at levels of 500 or 3000ppb had no significant effect on Ca retention. Gross et al (2014) reported that calcium phosphate materials in nano-size have higher specific surface area and surface roughness compared to conventional calcium phosphate materials. Therefore, nano-sized calcium phosphate materials have stronger interaction with organic materials.…”
Section: Table (2): Effect Of Dietary Nano Di-calcium Phosphate (Ndcpmentioning
confidence: 99%